Differences in Mathematical Reasoning Ability using the Discovery Learning Model and Contextual Teaching and Learning Model for Al-Asri Hessa Perlompongan Junior High School Students - Lela Agustina Panjaitan; Marah Dolly (JMEA : Journal of Mathematics Education and Application, 2022)
This type of research is semi-experimental. The purpose of this study was to determine if there was a difference in math proficiency among students using the discovery learning model and teaching and learning standards. Students of SMP Al-Asri Hessa Perlompongan. The population in this study were all VII SMP Al-Asri Hessa Perlompongan, totaling 6 classes, then sampling was done using random sampling technique. The samples taken were 2 classes, namely class VII-A and VII-B, each of which amounted to 29 students. The data collection tools used was pre-tests and post-tests in the questionnaire. Pre-tests are used to determine students' starting ability. On the other hand, post-hoc tests were used to determine differences in students' mathematical abilities after receiving different treatments. The hypothesis testing used is a 2-party t test with dk = 56 and ? = 0.05, then the obtained t count = 1.7623 and ttable = 1.67252 so that tcount ttable is 1.7623 1.67252 then H0 is rejected, thus it can be concluded that there are differences in students' mathematical reasoning abilities taught with the Discovery Learning learning model and the Contextual Teaching and Learning model Students of SMP Al-Asri Hessa Perlompongan.